Abundance of the Fanconi anaemia core complex is regulated by the RuvBL1 and RuvBL2 AAA+ ATPases - Rajendra, Eeson (Nucleic Acids Res, 2014)
Fanconi anaemia (FA) is a genome instability disease caused by defects in the FA DNA repair pathway that senses and repairs damage caused by DNA interstrand crosslinks. At least 8 of the 16 genes found mutated in FA encode proteins that assemble into the FA core complex, a multisubunit monoubiquitin E3 ligase. Here, we show that the RuvBL1 and RuvBL2 AAA+ ATPases co-purify with FA core complex isolated under stringent but native conditions from a vertebrate cell line. Depletion of the RuvBL1-RuvBL2 complex in human cells causes hallmark features of FA including DNA crosslinker sensitivity, chromosomal instability and defective FA pathway activation. Genetic knockout of RuvBL1 in a murine model is embryonic lethal while conditional inactivation in the haematopoietic stem cell pool confers profound aplastic anaemia. Together these findings reveal a function for RuvBL1-RuvBL2 in DNA repair through a physical and functional association with the FA core complex. Surprisingly, depletion of RuvBL1-RuvBL2 leads to co-depletion of the FA core complex in human cells. This suggests that a potential mechanism for the role of RuvBL1-RuvBL2 in maintaining genome integrity is through controlling the cellular abundance of FA core complex.